Early growth response-1: Key mediators of cell death and novel targets for cardiovascular disease therapy - Xie, Yixin; Li, Yongnan; Chen, Jianshu; Ding, Hong; Zhang, Xiaowei (Frontiers in Cardiovascular Medicine, 2023)
Significance: Cardiovascular diseases are seen to be a primary cause of death, and their prevalence has significantly increased across the globe in the past few years. Several studies have shown that cell death is closely linked to the pathogenesis of cardiovascular diseases. Furthermore, many molecular and cellular mechanisms are involved in the pathogenesis of the cardiac cell death mechanism. One of the factors that played a vital role in the pathogenesis of cardiac cell death mechanisms included the early growth response-1 (Egr-1) factor. Recent Advances: Studies have shown that abnormal Egr-1 expression is linked to different animal and human disorders like heart failure and myocardial infarction. The biosynthesis of Egr-1 regulates its activity. Egr-1 can be triggered by many factors such as serum, cytokines, hormones, growth factors, endotoxins, mechanical injury, hypoxia, and shear stress. It also displays a pro-apoptotic effect on cardiac cells, under varying stress conditions. EGR1 mediates a broad range of biological responses to oxidative stress and cell death by combining the acute changes occurring in the cellular environment with sustained changes in gene expression. Future Directions: The primary regulatory role played by the Egr-1-targeting DNAzymes, microRNAs, and oligonucleotide decoy strategies in cardiovascular diseases were identified to provide a reference to identify novel therapeutic targets for cardiovascular diseases.